2019
DOI: 10.1038/s41598-019-49271-1
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of ultrasound-guided fine-needle aspiration biopsy for transcriptome sequencing of the canine prostate

Abstract: Ultrasound-guided fine-needle aspiration (US-FNA) biopsy is a widely used minimally invasive sampling procedure for cytological diagnosis. This study investigates the feasibility of using US-FNA samples for both cytological diagnosis and whole transcriptome RNA-sequencing analysis (RNA-Seq), with the ultimate aim of improving canine prostate cancer management. The feasibility of the US-FNA procedure was evaluated intra vitam on 43 dogs. Additionally, aspirates from 31 euthanised dogs were collected for standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…Besides, we validated our results comparing our DEGs found in treated PC cell lines with gene expression profile of primary tumors (23). Interestingly, we found gene expression in opposite direction to that found in tumor tissues and these could be interesting genes to understand the modulation of toceranib phosphate therapy in these canine prostate carcinomas.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Besides, we validated our results comparing our DEGs found in treated PC cell lines with gene expression profile of primary tumors (23). Interestingly, we found gene expression in opposite direction to that found in tumor tissues and these could be interesting genes to understand the modulation of toceranib phosphate therapy in these canine prostate carcinomas.…”
Section: Discussionsupporting
confidence: 76%
“…We found 1,412 up and 668 downregulated genes shared by the primary tumors from biopsy and needle-aspiration (23). By comparing the gene expression profile of primary tumors with the treated cell lines we observed that PC1 has 59 overlapping genes while PC2 has 11 overlapping genes ( Figure 8A).…”
Section: Cell Lines Gene Expression Profile Validation In Primary Tumorsmentioning
confidence: 86%
See 1 more Smart Citation
“…Histological evaluation by ultrasound-guided fine needle aspiration (FNA) has been shown to be the most accurate test for detecting PN. Nevertheless, due to the low contrast and specificity existing between malignant areas and normal tissues on ultrasound images, nontargeted 12-site systematic biopsies covering the whole prostate gland are often performed to detect neoplasia, causing unnecessary pain to the patient [18][19][20]. Therefore, due to the lack of specific tumor ultrasonographic patterns, it is of great importance to develop innovative imaging techniques to increase the sensitivity and specificity of prostate cancer screening at an early stage, which may become very helpful to collect fewer and targeted samples, thereby reducing pain and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Canine prostate adenocarcinoma and transitional cell carcinoma are characterized by a local and invasive growth pattern and are clinically difficult to differentiate in dogs. Both tumors are associated with a poor prognosis due to late diagnosis, metastatic and invasive behavior, and limited therapeutic options [ 1 3 ]. Moreover, canine prostate adenocarcinoma is refractory to androgen deprivation therapy, which is the first-line therapy for prostate cancer in humans [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%